MINAT MAHASISWA FEBI IAIN LHOKSEUMAWE BERPROFESI DI PERBANKAN SYARIAH - Ismaulina Ismaulina Ismaulina (Jurnal Ilmiah Ekonomi Islam, 2023)
The need for human resources (HR) in various Islamic financial institutions in the Aceh province has increased since the enactment of Qanun no. 11 of 2018. In order to realize the Islamic economy of Aceh. Meanwhile, human resources who have the ability and knowledge of Islamic financial transactions are not adequate and adequate. This study aims to determine how the influence of attitudes, subjective norms, behavioral control, financial rewards, either partially or simultaneously on student interest in the Islamic banking profession. The population in this study amounted to 255 students of IAIN Lhokseumawe majoring in Islamic economics class 2015-2017. Sampling using purposive sampling and obtained 72 students. Data collection methods are through questionnaires, literature studies, and internet research. The results showed that attitude and behavior control had no effect on student work interest in Islamic banking as indicated by the value of Sig. 0.402 > 0.05 and the value of Sig. 0.652 > 0.05.While the subjective norm variables and financial rewards affect student interest in working in Islamic banking with the value of Sig. 0.000 < 0.05. Meanwhile, the simultaneous test shows that all independent variables have an effect on student work interest in Islamic banking.